Hypertension Does Not Alter the Increase in Cardiac Baroreflex Sensitivity Caused by Moderate Cold Exposure - Hintsala, Heidi E.; Kiviniemi, Antti M.; Tulppo, Mikko P.; Helakari, Heta; Rintamäki, Hannu; Mäntysaari, Matti; Herzig, Karl-Heinz; Keinänen-Kiukaanniemi, Sirkka; Jaakkola, Jouni J. K.; Ikäheimo, Tiina M. (Frontiers in Physiology, 2016)
Exposure to cold increases blood pressure and may contribute to higher wintertime cardiovascular morbidity and mortality in hypertensive people, but the mechanisms are not well established. While hypertension does not alter responses of vagally-mediated heart rate variability to cold, it is not known how hypertension modifies baroreflex sensitivity and blood pressure variability during cold exposure. Our study assessed this among untreated hypertensive men during short-term exposure comparable to habitual winter time circumstances in subarctic areas. We conducted a population-based recruitment of 24 untreated hypertensive and 17 men without hypertension (age 55-65 years) who underwent a whole-body cold exposure (-10°C, wind 3m/s, winter clothes, 15 min, standing). Electrocardiogram and continuous blood pressure were measured to compute spectral powers of systolic blood pressure and heart rate variability at low (0.04-0.15 Hz) and high frequency (0.15-0.4 Hz) and spontaneous baroreflex sensitivity at low frequency. Comparable increases in baroreflex sensitivity were detected in hypertensive men, from 2.6 (2.0, 4.2) to 3.8 (2.5, 5.1) ms/mmHg (median (interquartile range)), and in control group, from 4.3 (2.7, 5.0) to 4.4 (3.1, 7.1) ms/mmHg. Instead, larger increase (p<0.05) in low frequency blood pressure variability was observed in control group; response as median (interquartile range): 8 (2, 14) mmHg², compared with hypertensive group (0 (-13, 20) mmHg²). Untreated hypertension does not disturb cardiovascular protective mechanisms during moderate cold exposure commonly occurring in everyday life. Blunted response of the estimate of peripheral sympathetic modulation may indicate higher tonic sympathetic activity and decreased sympathetic responsiveness to cold in hypertension.